2009
DOI: 10.1007/s00382-008-0520-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability and predictability of summer monsoon onset over the Philippines

Abstract: The spatio-temporal variability of boreal summer monsoon onset over the Philippines is studied through the analysis of daily rainfall data across a network of 76 gauges for the period 1977 to 2004 and the pentad Merged Analysis of Precipitation from the US Climate Prediction Center from 1979 to 2006. The onset date is defined using a local agronomic definition, namely the first wet day of a 5-day period receiving at least 40 mm without any 15-day dry spell receiving less than 5 mm in the 30 days following the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 42 publications
4
43
0
2
Order By: Relevance
“…S.J., the Chief of the Manila Observatory’s Meteorological Division. In the succeeding years, the Philippine Atmospheric Geophysical and Astronomical Services Administration (PAGASA) adopted and modified the classification, which is now known as the Modified Coronas classification [26]. There are four climate types, namely Type I, II, III, and IV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S.J., the Chief of the Manila Observatory’s Meteorological Division. In the succeeding years, the Philippine Atmospheric Geophysical and Astronomical Services Administration (PAGASA) adopted and modified the classification, which is now known as the Modified Coronas classification [26]. There are four climate types, namely Type I, II, III, and IV.…”
Section: Methodsmentioning
confidence: 99%
“…Type III, on the other hand, resembles Type I, but with maximum rainfall periods from May to October. Lastly, Type IV has a more or less even distribution of rainfall year-round [26,28]. …”
Section: Methodsmentioning
confidence: 99%
“…First of all, we examined model ability to capture major mesoscale and regional-scale climate features based on seasonal evolution in a synoptic scale domain, which influence basin-scale inter-seasonal precipitation. For examples, a pronounced Asia Pacific southwest monsoon system from May to November over Luzon Island in the Philippines (Murakami and Matsumoto, 1994;Moron et al, 2009), strong seasonal frontal systems and typhoons stirring around the Yoshino River from June 10 to November (Tachikawa et al, 2009), effects of the east Asian and south Asian monsoons and Tibetan Plateau high on the Kalu Ganga River, impacts of Mediterranean climate that include parts of Europe, and Mediterranean Sea and eastern Atlantic Ocean influences on the Medjerda River basin. Detailed information of local and regional domains, catchment areas, climate zones and number of stations is given in Table 1.…”
Section: Decrement Of Gcm Uncertaintymentioning
confidence: 99%
“…In addition, it is well known that the seasonality of rainfall in the Philippines is largely affected by the El Niño-Southern Oscillation (ENSO) (Lyon et al 2006;Lyon and Camargo 2009;Moron et al 2009). For example, Ropelewski and Halpert (1987) showed that the El Niño brings about drier conditions around the Philippines between June and November.…”
Section: Introductionmentioning
confidence: 99%
“…Moron et al (2009) used rainfall data collected at 76 stations between 1977 and 2004 and data from the Climate Prediction Center Merged Analysis of Precipitation (CMAP) from 1979 to 2005 to study the spatial and temporal variability of the onset of the summer monsoon and to assess the seasonal predictability of local onset dates. They identified important climatic factors that are essential for the prediction of the onset: the sea surface temperature (SST) over the tropical Pacific and Indian Oceans in March and the wind field at the 850 hPa level in May.…”
Section: Introductionmentioning
confidence: 99%